Investigation of demographic characteristics and incidence of ocular injuries: a retrospective study - Agiant, Samira; Marvaki, Christina; Govina, Ourania; Papaconstantinou, Dimitris; Diagourtas, Andreas; Papageorgiou, Dimitris (Health & Research Journal, 2018)
Introduction: Ocular trauma is a common cause of visual reduction or loss and relates with a variety of demographic factors. Aim: Investigating the relationship of patients with eye injuries demographic data who were operated in a Public Hospital of the Attica Prefecture with place of accident, cause, classification and complications of trauma. Material and Methods: This is a retrospective study. The sample consisted of 219 patients with ocular trauma who underwent a surgical therapy. For data collection a specific registration form was used. Data analysis was performed with the statistical package Statistical Package for Social Sciences (SPSS) ver.22. Results: The relationship of gender and age of patients, with place of injury, classification and etiology of trauma was statistically significant (p <0.05). The 56.7% of women reported home related injuries, mainly due to falls, while 96.8% of men reported work related injuries. The mean age of those patients injured at home was 68.15 years, while at work was 42.79 years. Statistically significant was the relationship between nationality and the place of injury and complications (p<0.05). The 94% of Greek patients reported injury mainly at home, while the 25.8% of the foreigners reported injury at work, with post-traumatic endophthalmitis in 66.7% of them, mainly in rural areas. Conclusions: The investigation of relationship between the demographic data and ocular trauma is a challenge for the development of strategies prevention.